Tourism beyond limits: A systematic review on the challenges and mitigation strategies of overtourism - Hanafie, Aryawidya Aulia; Nurhaliza, Hannissa Destriwani; Ramadhan, Muhammad At Thariq; Prasetya, Nabila Zahra Nur; Putri, Nasywa Rizqia; Widaningsih, Neni; Rahmafitria, Fitri (ASEAN Natural Disaster Mitigation and Education Journal, 2025)
Background: Tourism in Bali has grown rapidly, driving economic growth but exacerbating overtourism, where visitor numbers exceed capacity. This leads to environmental damage, resource depletion, and socio-economic problems. Methods: This study uses a Systematic Literature Review (SLR) approach, focusing on publications from 2020 to 2024 from both international and national journals, identifying dominant themes such as environmental, economic, and cultural challenges. Findings: The results reveal that overtourism in Bali significantly affects environmental, economic, and cultural aspects. Strategies such as equitable tourist distribution, infrastructure development in less-developed areas, and sustainable tourism policies are crucial to addressing these challenges. Policies such as tourist limitations (enforcing visiting hours) and restrictions on tourist business development can also help reduce overtourism in Bali. Conclusion: A case study of Nusa Dua highlights capacity management efforts, including event access limitations and stakeholder collaboration, which have been implemented effectively. Nusa Dua not only cooperates with the government and surrounding entrepreneurs, but also with the local community, especially when there are big events being organized. Novelty/Originality of this article: Additionally, this study provides a new perspective by examining how overtourism impacts local communities' connection to their traditions culture, while emphasizing the balance between economic growth, preserving nature and cultural preservation in sustainable tourism.